Cucurbitacin B inhibits growth, arrests the cell cycle, and potentiates antiproliferative efficacy of cisplatin in cutaneous squamous cell carcinoma cell lines - Chen, Weikai; Leiter, Amanda; Yin, Dong; Meiring, Muriel; Louw, Vernon J.; Koeffler, H. Phillip (Spandidos Publications, 2010)
Cutaneous squamous cell carcinoma (CSCC) is the second most common skin cancer with a substantial risk of metastasis which causes clinical treatment failure. This study investigated the anti-CSCC effects of a triterpenoid compound, Cucurbitacin B (CuB). Dose-response studies showed that CuB inhibited 50% growth (ED50) of the CSCC cell lines (SRB1, SRB12, SCC13, COLO16) in liquid culture at 4x10-7 -10-5 M. Soft-agar assays demonstrated that nearly all of the CSCC clonogenic cells were inhibited at 10-7 M CuB. FACS analysis found that the compound (10-7 M, 48 h) caused G2/M arrest. The CSCC cells underwent profound morphologic changes within 60 min after exposure to CuB (10-7 M), rounding up and losing their pseudopodia. CuB (10-7 M) caused prominent multinucleation of the cells after they were pulse-exposed (24 h) to the drug, washed and cultured in normal medium for an additional 24 h. The drug (10-8-10-6 M, 3-24 h) decreased levels of CDC2 and cyclin B1 in SRB1 and SRB12 cell lines as seen by Western blot analysis. Migration of SRB1 and SRB12 cells was inhibited by 10-7 M CuB. Interestingly, CuB synergistically potentiated the anti-proliferative effect of cisplatin in CSCC. In summary, CuB has a prominent anti-proliferative activity on CSCC cells. In vivo studies and clinical trials of this drug should be pursued in CSCC.
Keywords: Cucurbitacin B; Cell cycle; Cisplatin; Cutaneous squamous cell carcinoma; Skin -- Cancer; Squamous cell carcinoma